Single-cell RNA sequencing reveals immunological rewiring at the maternal-fetal interface following asymptomatic/mild SARS-CoV-2 infection - Suhas Sureshchandra; Michael Z. Zulu; Brianna M. Doratt; Allen Jankeel; Delia Tifrea; Robert Edwards; Monica Rincon; Nicole E. Marshall; Ilhem Messaoudi (Cell Reports, 2022)
Summary: While severe coronavirus 2019 (COVID-19) is associated with immune activation at the maternal-fetal interface, responses to asymptomatic/mild severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection during pregnancy remain unknown. Here, we assess immunological adaptations in blood and term decidua in response to asymptomatic/mild disease in pregnant women. We report attenuated antigen presentation and type I interferon (IFN) signaling pathways, loss of tissue-resident decidual macrophages, and upregulated cytokine/chemokine signaling in monocyte-derived decidual macrophages. Furthermore, we describe increased frequencies of activated tissue-resident T cells and decreased abundance of regulatory T cells with infection while frequencies of cytotoxic CD4/CD8 T cells are increased in the blood. In contrast to decidual macrophages, type I IFN signaling is higher in decidual T cells. Finally, infection leads to a narrowing of T cell receptor diversity in both blood and decidua. Collectively, these observations indicate that asymptomatic/mild COVID-19 during pregnancy results in remodeling of the immunological landscape of the maternal-fetal interface, with a potential for long-term adverse outcomes for the offspring.